RÉQUIEM PARA MATRAGA E BACURAU: A Canção de Geraldo Vandré e sua Contribuição para a Narrativa Fílmica – uma Abordagem pela Semiótica da Cultura - Christani, Eric Ribeiro (2022)
Through the semiotics of culture, used in the present work as an analysis tool, we studied the insertion of the song Requiem para Matraga, by Geraldo Vandré, as a song of the film Bacurau (2019), by Juliano Dornelles and Kleber Mendonça Filho. In order to analyze the effects produced by music on the narrative, film analysis methods were applied. Bibliographic surveys, journalistic materials and news sites were carried out to understand the respective contexts of the song and the film and their authors in the articulations with the concepts related to the semiotics of culture, such as semiosphere, border, cultural text and cultural memory used in the analysis. It was observed that aspects such as historical context, musical authorship and cultural memory value of music add meaning to the narrative.(AU)